Eco-Energetical analysis of circular economy and community-based virtual power plants (CE-cVPP): A systems engineering-engaged life cycle assessment (SE-LCA) method for sustainable renewable energy development - Xie, Haonan; Goh, Hui Hwang; Zhang, Dongdong; Sun, Hui; Dai, Wei; Kurniawan, Tonni Agustiono; Dennis Wong, M.L.; Tze Kin Teo, Kenneth; Goh, Kai Chen (Elsevier, 2024)
Amidst the escalating complexity of energy demands and climate concerns, natural calamities, and the Black Swan phenomenon have all presented formidable obstacles to the advancement and implementation of Abbreviations: AI, Artificial intelligence; CBD, Central business district; CE, Circular economy; CE-cVPP, Circular economy and community-based virtual power plant; COP, Coefficient of performance; cVPP, Community-based virtual power plant; DER, Distributed energy resources; EC, Electric chiller; FLCA, Full lifecycle assessment; FLC-APERR, Full-lifecycle atmospheric pollutants emission reduction ratio; FLC-ATCSR, Full-lifecycle annual total cost saving ratio; FLC-PESR, Fulllifecycle primary energy saving ratio; GB, Gas boiler; GSHP, Geothermal source heat pump; HHV, Higher heating value; HX, Heat exchanger; ICE, Internal com bustion engine; IES, Integrated energy system; LCA, Life cycle assessment; LHV, Lower heating value; MG, Micro-grid; ORC, Organic Rankine cycle; PV, Photovoltaic; SDGs, Sustainable development goals; SE, Systems engineering; SE-LCA, Systems engineering-based life cycle assessment; TES, Thermal energy storage; VESS, Virtual energy storage system.